Heat Reduction on Light Emitting Diode Solar Simulator - Cut Nurmuthaharah; Ira Devi Sara; Tarmizi Tarmizi (Institute for Research and Community Service (LPPM), Universitas Malikussaleh, Indonesia, 2024)
LED solar simulator converts electrical energy into light and heat. The resulting heat effect apply damage to the LED and affect performance and accuracy test. Despite being equipped with a heatsink and fan cooling system, the temperature of the LED solar simulator is still considerably quite high though it is necessary to lowered the temperature even further to increase its service life. One major challenge faced is the management of the heat generated by the LEDs. This article aims to investigate the effect of placing a copper pipe-based cooling system containing refrigerant R32 and Thermoelectric to reduce the temperature of the LED solar simulator by at least 10%. The use of thermoelectric cooler (type 12706) as an alternative cooling technology is safer for surrounding environment compared to vapor compression. Copper pipes were chosen for better conductivity, flexibility and better heat absorbance, meanwhile refrigerant R32 were chosen for it is environmentally friendly and possess a lower GWP. The test results illustrate the application of a copper pipe-based cooling system containing refrigerant R32 and thermoelectric succeeded in reducing the temperature of the LED solar simulator by 11,41% and increased the level of radiation uniformity from an average of 422 W/m² to 429 W/m² with a depreciation of non-uniformity of 0,84%. Thus, this very combination cooling system is proven effectively reducing the temperature of the LED solar simulator by at least 10%.